Analisis Valuasi Startup Studi Kasus Beritabali.com - I Luh Made Sischa Octarina; Ni Made Estiyanti; I Putu Agus Swastika (STMIK Pringsewu, 2022)
A startup is a company that has innovative ideas and is often associated with technology. However, many Startups fail, one of which is due to a lack of knowledge and lack of funds. To get funds from investors, Startups must prepare a valuation value that will later be taken into consideration by investors. Beritabali.com is one of the Startups that requires a valuation value which is then used to find investors. The method used to find the valuation value of Beritabali.com is the scorecard valuation method. The scorecard valuation method is a valuation method that measures the value of the company from non-financial aspects. The valuation value of beritabali.com obtained from this method is Rp. 2,994,333,332. Meanwhile, the Present Value of Beritabali.com, which is measured from a financial point of view, is Rp. 780,797,764,-.